Numerical study on convective boundary layer flow and heat transfer of nanofluid over a wedge / Ruhaila Md. Kasmani - Ruhaila , Md. Kasmani (2016)
The convective boundary layer flow,. heat (and mass) transfer of nanofluid over a wedge are investigated. The fluid flow and heat transfer characteristics of nanofluid have received considerable attention due to wide range of engineering applications. In many boundary layer flow studies, it is found that nanofluid exhibits higher thermal conductivity and heat transfer coefficients compared to the conventional fluid. In this thesis, the mathematical nanofluid model proposed by Buongiomo is used to study the boundary layer flow of nanofluid past a wedge under the influence of various effects. The nanofluid model takes into account the transport mechanism of nanoparticles, namely the Brownian diffusion and thermophoresis. Based on this model, the mathematical formulation is developed to study the characteristics of flow, heat (and mass) transfer of six boundary layer flow problems. The problems are limited to steady, two-dimensional, laminar flow of incompressible viscous nanofluid along a wedge. The governing partial differential equations are reduced to a system of nonlinear ordinary differential equations using similarity transformation. The resulting system is solved numerically using the fourthorder Runge-Kutta-Gill method along with the shooting technique and Newton Raphson method. Then, the numerical values of the skin friction, heat (and mass) transfer coefficients are obtained for various values of the governing parameters such as wedge angle, heat generation/absorption, thermal radiation, Brownian motion, thermophoresis, suction, power law variation, Soret and Dufour effects. Comparisons with previously published work for verification and accuracy of the method used is performed and found to be in good agreement. The solutions are expressed graphically in terms of velocity, temperature, solutal concentration and nanoparticle volume fraction profiles. The effects of pertinent parameters entering into the problems on skin friction coefficient, local Nusselt number and local Sherwood number are discussed in detail.